Simultaneous selection for fruit quality and resistance to late blight in tomato progenies - Nick, Carlos; Laurindo, Bruno Soares; Almeida, Victor de Souza; Freitas, Renata Dias de; Aguilera, Jorge González; Silva, Eduardo Chagas Ferreira da; Cruz, Cosme Damiao; Silva, Derly Jose Henriques da (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate selection criteria in progenies from the crossing of tomato cultivar Santa Clara (Solanum lycopersicum) and the wild species S. habrochaites f. glabratum as to attributes of fruit quality and of resistance to late blight (Phytophthora infestans). The families were evaluated in a randomized block design, in two trials, with two replicates and six controls, common to both trials. Direct and indirect gains were estimated between F2:3 families for simultaneous selection regarding resistance to late blight, determined by the quantification of the area under the disease progress curve (AUDPC), and regarding titratable acidity and soluble solid contents of fruit. The selection criteria provided satisfactory genetic gains, suitable for the proposed ideotype of decreases in the AUDPC and increases in the average values of soluble solids and titratable acidity. The direct and indirect selection and the Mulamba & Mock index result in more balanced individual gains and higher total gains.